Possibilities for the domestication of bluefin tunas in the Eastern Mediterranean sea - Oray I.K.; Karakulak F.S. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
Turkey borders the Black Sea, the Sea of Marmara, the Aegean and the Mediterranean Seas with a total coast line of 8333 km. The Mediterranean coast is 1839 km long. The water temperatures on the Mediterranean coasts of Turkey are good to grow out the bluefin tunas. The monthly minimum mean surface water temperatures in the Western Turkish Mediterranean Coast in Antalya in the coldest month in February was 16.6 degrees C. In the hottest month in August the maximum mean surface water temperature was 27.6 degrees C.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)